INITIATING MANAGEMENT STRATEGY FOR ISLAMIC EDUCATIONAL INSTITUTIONS TO ENHANCE THE QUALITY OF ISLAMIC HUMAN RESOURCES - Rizal, Moh. (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Islamic educational institutions, especially MTsN 1 Lumajang, are expected to produce high-quality human resources who are faithful and devout, possessing insights into science and technology. The objectives of this research are as follows: 1) To identify challenges that act as obstacles in the process of improving human resources quality in educational institutions at MTsN 1 Lumajang. 2) To discover solutions in the process of enhancing human resources quality in educational institutions at MTSN 1 Lumajang. 3) To describe the strategies and management techniques implemented by the educational institution MTSN 1 Lumajang to improve human resources quality. 4) To understand the factors influencing the improvement of human resources quality. The results of this research show that in enhancing the quality of Islamic human resources, educational institutions play a crucial role in the process of improving human resources quality. The improvement of education quality is an integrated process, supported by facilities, willingness to enhance educational quality, appropriate compensation, and the management and leadership of the educational institution. Recognizing the importance of improving the quality of human resources, the government, educational institution managers, educators, and participants strive to achieve these goals, visions, and missions.